Economic Benefits of Rural Feeder Roads: Evidence from Ethiopia. Issue 9 (1st September 2016) - Stifel, David; Minten, Bart; Koru, Bethlehem
Abstract: We estimate households' willingness-to-pay for rural feeder roads in Ethiopia. Using purposefully collected data, we compare the economic behaviour of households by remoteness to estimate the benefits of access to feeder roads. Although we cannot definitively assert a causal relationship, we cautiously estimate that gravel roads have internal rates of return of 12–35 per cent. These results suggest that rural feeder roads may have relatively high rates of return even in unfavourable settings where (a) small-scale farmers have low levels of marketed agricultural surplus, (b) non-farm earning opportunities are negligible, and (c) motorised transport services are not guaranteed.